99mTC-sestamibi breast imaging: Current status, new ideas and future perspectives. (September 2022) - Urbano, Nicoletta; Scimeca, Manuel; Tancredi, Virginia; Bonanno, Elena; Schillaci, Orazio
Abstract: Here we proposed the most recent innovations in the use of Breast Specific Gamma Imaging with 99 mTc-sestamibi for the management of breast cancer patients. To this end, we reported the recent discoveries concerning: a) the implementation of both instrumental devices and software, b) the biological mechanisms involved in the 99 mTc-sestamibi uptake in breast cancer cells, c) the evaluation of Breast Specific Gamma Imaging with 99 mTc-sestamibi as predictive markers of metastatic diseases. In this last case, we also reported preliminary data about the capability of Breast Specific Gamma Imaging with 99 mTc-sestamibi to identify breast cancer lesions with high propensity to form bone metastatic lesions due to the presence of Breast Osteoblast-Like Cells.